Memorandum of understanding between Universiti Teknologi MARA and University of Malaya (University Malaya Medical Centre) / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2021)
UiTM and UM Medical Centre will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.